Some geometric aspects of polyvalent systems modeling - Grinis, Irus; Ivanauskas, Feliksas; Stepanauskas, Gediminas (Lietuvos matematikos rinkinys, 2012)
In this paper we consider the interaction of ligands and receptors on the plane and in the space.